O imaginário tecendo o real: números reais, valores imaginários. Análise discursiva-simbólica do enunciado valor de mercado - Silva, Samuel de Sousa (2018)
This paper is a study about the capitalist discourse materialized in the sentence "market value". The research corpus is the Forbes List of the most important companies of the world in 2016. The theoretical references used in this research are the next: Discourse analysis of the french line and the Imaginary Anthropology. The research analyzes the supremacy of the symbolic percentage of this concept over its real/material percentage and the implicit social contract of valuation of the symbolic over the real. The Discourse Analysis helps in verifying the historical constitution of this discourse, its affiliations and derivations related to christian religious discourse. The Imaginary Anthropology operates the mitocriticism which intends to fragment the mythical constitution of this discourse. The fundamental theoretical concepts which is based this analysis will be: the concept of the production conditions and of interdiscourse of the French Discourse Analysis; and the Lacan's metonymic object, applied to capitalist discourse by Baudrillard. These analysis shows a estrategy of the capitalist discourse, which construtes metaphorical concepts that refer to central doctrines of Christian theology. These concepts are invested into objects of consumption of capitalism like metonymic representations of these metaphors. So, these paper concludes that Forbes list's discourse updates the ascensional narrative biblical myth of the Babel tower to the contemporary capitalist society.